Neutrophilic alveolitis in Sweet's syndrome. - Bourke, S J (1992)
In a case of Sweet's syndrome (acute febrile neutrophilic dermatosis) neutrophilic alveolitis was found by lung biopsy. Pulmonary disease in this condition may be underrecognised yet, like the dermatological features, it responds rapidly to corticosteroids.